2001
DOI: 10.1038/ng766
|View full text |Cite
|
Sign up to set email alerts
|

The contributions of sex, genotype and age to transcriptional variance in Drosophila melanogaster

Abstract: Here we present a statistically rigorous approach to quantifying microarray expression data that allows the relative effects of multiple classes of treatment to be compared and incorporates analytical methods that are common to quantitative genetics. From the magnitude of gene effects and contributions of variance components, we find that gene expression in adult flies is affected most strongly by sex, less so by genotype and only weakly by age (for 1- and 6-wk flies); in addition, sex x genotype interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
440
2
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 576 publications
(465 citation statements)
references
References 20 publications
21
440
2
2
Order By: Relevance
“…1A). Recent work has shown that sex-biased gene expression is significant in Drosophila (6)(7)(8). This first report of sex-biased expression of the full (predicted) genome also strongly indicates that there is significant sex-biased expression-especially in gonads (Fig.…”
mentioning
confidence: 88%
“…1A). Recent work has shown that sex-biased gene expression is significant in Drosophila (6)(7)(8). This first report of sex-biased expression of the full (predicted) genome also strongly indicates that there is significant sex-biased expression-especially in gonads (Fig.…”
mentioning
confidence: 88%
“…ANOVA analysis has been used in several microarray studies (30)(31)(32) to account for the variations in gene expressions caused by different sources, and normalization was included as part of their models. Our analysis has separated the normalization procedure from significance inference, which identifies differentially expressed genes more reliably (33).…”
Section: Discussion Factorial Analysis Can Effectively Identify Relevmentioning
confidence: 99%
“…The ratio function method (Chen et al, 1997) assumes that the coefficients of variation of the two channels are the same. The ANOVA methods (Kerr et al, 2000;Jin et al, 2001;Wolfinger et al, 2001) adjust for overall effects of array and dye across genes. Since the background subtraction and normalization steps have been addressed elsewhere (Yang et al, 2002a;Quackenbush, 2001;Quackenbush, 2002), this paper will focus on the transformation step.…”
Section: Introductionmentioning
confidence: 99%